Daughter-mother perspectives on feminist activism in the academy. (January 2023) - Reedy, Florence; Haynes, Kathryn
This article addresses feminist solidarity between a daughter and a mother in academia. We are respectively a PhD student and aspirant early career academic, and a senior academic, both identifying as feminists and engaging in forms of activism to improve gender equality. We take an autoethnographical approach, drawing from vignettes and conversational dialogues, focusing on feminist perspectives, activism, our contested identities, fears and hopes. We reflect on the challenges of living feminist lives whilst working in gendered university institutions and highlight strategies to enact feminism whilst trying to progress and maintain an academic career at different positions on the career spectrum. Our contribution is to highlight differential experiences and understandings of academic activism between daughter and mother, early-career academics and senior leaders, in order to enhance mutual understanding and action on feminist solidarity and praxis in the academy.